2003
DOI: 10.1021/ef030096t
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Emissions and Fuel Economy from Hybrid-Electric and Conventional-Drive Transit Buses

Abstract: Hybrid-electric transit buses offer potential benefits over conventional transit buses of comparable capacity, including reduced fuel consumption, reduced emissions, and the utilization of smaller engines. Emissions measurements were performed on a 1998 New Flyer 40-foot transit bus equipped with a Cummins ISB 5.9-L diesel engine, an Engelhard DPX catalyzed particulate filter, and an Allison series-drive system. Results were compared to a conventional-drive, diesel-powered bus that was equipped with an oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…However, most of the HC mass consisted of methane. Emissions from NGB across North America and Europe have been well-documented in numerous published studies (Wang et al 1993;Clark et al 1997;McCormick et al 1999;Weaver et al 2000;Wayne et al 2004;.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, most of the HC mass consisted of methane. Emissions from NGB across North America and Europe have been well-documented in numerous published studies (Wang et al 1993;Clark et al 1997;McCormick et al 1999;Weaver et al 2000;Wayne et al 2004;.…”
Section: Introductionmentioning
confidence: 91%
“…They were also found to produce low CO and HC emissions. Previous results (McKain et al 2000;CASE 2001;Bass and Alfermann 2003;Wayne et al 2004;Chandler and Walkowicz, 2006; showed that the average NOx emissions from hybrid-electric diesel buses were about 25-30% lower than those from conventional diesel buses while average FE of the hybrid-electric diesel buses was about 20-25% higher than that from diesel buses. However, the percentage of FE benefit from the hybrid buses was route (or cycle) dependant.…”
Section: Introductionmentioning
confidence: 94%
“…The hybrid bus and one of the CNG buses had the lowest CO emissions, and the hybrid bus and buses equipped with continuously regenerated trap (CRT) exhaust aftertreatment had hydrocarbon emissions that were below the detectable limit of the instrument used. Wayne et al (2004) evaluated three transit vehicles, a seriesdrive hybrid-electric, a conventional drive diesel-powered, and a conventional-drive liquefied natural gas (LNG)-powered bus. They evaluated the buses on a chassis dynamometer over several cycles.…”
Section: Introductionmentioning
confidence: 99%
“…There were many possibilities made local concentration of PM 2.5 unstable, including the type of bus engine, emission frequency, and convection condition. The diesel engines have been shown to emit higher level of particulate emission (Wayne et al, 2004;Bitterman and Hess, 2008).…”
Section: Atmospheric Pm 25 Mass Concentration Level Around Bus Stationmentioning
confidence: 99%